Association between the risk for lung adenocarcinoma and a (−4) G-to-A polymorphism in the XPA gene - Butkiewicz, Dorota; Popanda, Odilia; Risch, Angela; Edler, Lutz; Dienemann, Hendrik; Schulz, Volker; Kayser, Klaus; Drings, Peter; Bartsch, Helmut; Schmezer, Peter (Cancer epidemiology, biomarkers & prevention, 2004)
Polymorphisms of genes coding for DNA repair can affect lung cancer risk. A common single nucleotide (−4) G-to-A polymorphism was identified previously in the 5′ untranslated region of the XPA gene. In a case-control study in European Caucasians, the influence of this polymorphism on primary lung cancer risk overall and according to histologic subtypes was investigated. Four hundred sixty-three lung cancer cases (including 204 adenocarcinoma and 212 squamous cell carcinoma) and 460 tumor-free hospital controls were investigated using PCR amplification and melting point analysis of sequence-specific hybridization probes. Odds ratios (OR) were calculated by multiple logistic regression analysis adjusting for age, gender, smoking habits, and occupational exposure and showed a slightly enhanced risk for all lung cancer cases as well as for squamous cell carcinoma and adenocarcinoma cases. Gene-environment interactions were analyzed with respect to smoking and occupational exposure. A nearly 3-fold increased risk for adenocarcinoma associated with the XPA AA genotype was observed for occupationally exposed individuals (OR, 2.95; 95% confidence interval, 1.42-6.14) and for heavy smokers (OR, 2.52; 95% confidence interval, 1.17-5.42). No genotype-dependent increase in OR was found for nonexposed individuals or those smoking <20 pack-years. The significant effect of the XPA polymorphism in heavy smokers and occupationally exposed individuals suggests an important gene-environment interaction for the XPA gene. The underlying mechanisms as to why AA homozygotes are predisposed to lung adenocarcinoma and which specific carcinogens are involved remains to be determined.